2021
DOI: 10.3389/fmars.2021.721291
|View full text |Cite
|
Sign up to set email alerts
|

Response of Abundance and Distribution of Humboldt Squid (Dosidicus gigas) to Short-Lived Eddies in the Eastern Equatorial Pacific Ocean From April to June 2017

Abstract: In this study, the eddy characteristics on the fishing ground of the Humboldt squid (Dosidicus gigas) in the eastern equatorial Pacific Ocean were detected based on geometrical characteristics with the flow field during April–June 2017. The influence of the eddies on the biophysical environment, D. gigas abundance, and habitat distribution were explored. The habitat was identified by fishery data, sea surface temperature (SST), vertical water temperature, and chlorophyll-a (Chl-a). Results indicated that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Meanwhile, our results indicated that the debate concerning eddy‐induced high trophic organism distribution in previous studies is largely attributed to different spatial areas. Most previous case studies supporting high trophic organisms preferring anticyclonic eddies appeared in our revealed hotspots of the midlatitude oceans, such as swordfish in the Kuroshio Extension System (Durán Gómez et al, 2020), loggerhead sea turtles in the Brazil‐Malvinas Confluence region (Gaube et al, 2017), and sharks in the Gulf Stream (Braun et al, 2019; Gaube et al, 2018), while the case studies supporting that they prefer cyclonic eddies or have no obvious preference largely appeared in the lower latitude ocean, such as loggerhead sea turtles in the East China Sea (Kobayashi et al, 2011), cetacean species and bluefin tuna in the Gulf of Mexico (Davis et al, 2002; Teo & Block, 2010), squid in the Eastern Equatorial Pacific (Fang et al, 2021), and tuna species in the Mozambique Channel (Potier et al, 2014). These previous cases can be regarded as a subset of our revealed hotspots and support our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, our results indicated that the debate concerning eddy‐induced high trophic organism distribution in previous studies is largely attributed to different spatial areas. Most previous case studies supporting high trophic organisms preferring anticyclonic eddies appeared in our revealed hotspots of the midlatitude oceans, such as swordfish in the Kuroshio Extension System (Durán Gómez et al, 2020), loggerhead sea turtles in the Brazil‐Malvinas Confluence region (Gaube et al, 2017), and sharks in the Gulf Stream (Braun et al, 2019; Gaube et al, 2018), while the case studies supporting that they prefer cyclonic eddies or have no obvious preference largely appeared in the lower latitude ocean, such as loggerhead sea turtles in the East China Sea (Kobayashi et al, 2011), cetacean species and bluefin tuna in the Gulf of Mexico (Davis et al, 2002; Teo & Block, 2010), squid in the Eastern Equatorial Pacific (Fang et al, 2021), and tuna species in the Mozambique Channel (Potier et al, 2014). These previous cases can be regarded as a subset of our revealed hotspots and support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These previous cases can be regarded as a subset of our revealed hotspots and support our findings. Existing case studies usually focus on the abundance difference of high trophic organisms between anticyclonic eddies and cyclonic eddies, and comparisons between the two‐polarity eddy and outside eddy regions are absent (Arur et al, 2014; Braun et al, 2019; Durán Gómez et al, 2020; Fang et al, 2021; Gaube et al, 2018; Tew Kai & Marsac, 2010). Considering the effects of eddy‐occupied areas, our findings showed a more direct and overall relationship between mesoscale eddies and potential fish distribution by comparing the fishing activities per unit area between the anticyclonic eddy/cyclonic eddy and outside eddy regions, which provided reliable evidence that anticyclonic eddy (cyclonic eddy) regions were beneficial (detrimental) to their aggregation relative to outside eddy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of equatorial regions using the maximum entropy model have shown that D. gigas prefers to inhabit areas with relatively low eddy kinetic energy [30]. The eddy pumping induced by eddies provides abundant nutrients for D. gigas, creating high-quality habitats within the eddies [31].…”
Section: Introductionmentioning
confidence: 99%